Introduction of Kanban System in a Production Company Roland International Poland Limited Liability Company - Natalia PAWLAK; Dominika DŁUGONSKA; Marcin ANDRYSZAK (Communications of International Proceedings, 2021)
The purpose of this paper is to present the Kanban system. The first section discusses the meaning of the term Kanban. This is followed by a description of how the company functioned before and after the introduction of the Kanban system. The article concludes with a summary and recommendations.
Keywords: Kanban; Lean Management; Milkrun.